High-Throughput LC-MS/MS Method for Determination of the Alcohol Use Biomarker Phosphatidylethanol in Clinical Samples by Use of a Simple Automated Extraction Procedure—Preanalytical and Analytical Conditions. (1st May 2018) - Isaksson, Anders; Walther, Lisa; Hansson, Therese; Andersson, Anders; Stenton, Joanna; Blomgren, Anders
Abstract: Background: Phosphatidylethanol (PEth) is an alcohol use biomarker with higher clinical sensitivity and specificity than commonly used alcohol markers. Since its introduction as a clinical alcohol-marker in 2006, the number of samples sent to our laboratory for the determination of PEth has shown a strong annual increase. This has prompted the need to develop a cost-effective and reliable analytical procedure with high capacity. Methods: An LC-MS/MS method for the determination of PEth 16:0/18:1 with a short turnaround time (3 min) has been evaluated with respect to accuracy, sensitivity, and precision. We compared this method with a previously used HPLC method, as well as a manual and a simplified automated method for sample workup, and investigated potential causes of analytic and preanalytic errors. Results: The method shows limits of detection and quantification of 0.0075 μmol/L (5.2 ng/mL) and <0.05 μmol/L (<35 ng/mL), respectively. During a 2.1-year period, the method has shown a total CV < 8% for control samples (n = 2808) in the range of 0.10 (70) to 3.5 μmol/L (2461 ng/mL). The simplified automated method for sample preparation works equally well as the manual one. No specific and clinically significant causes of preanalytic errors were found. Conclusions: This LC-MS/MS method with automated sample workup is well suited for a clinical laboratory with LC-MS/MS experience and has the capability, proven from several years of use, to produce reliable PEth results in a high-volume laboratory (>50000 clinical samples/year).